The Effects of Feeding on Cardiac Control of the Broad-Nosed Caiman (Caiman latirostris): The Role of the Autonomic Nervous System and NANC Factors - Braga, Victor Hugo Da Silva [UNESP]; Armelin, Vinicius Araújo [UNESP]; Teixeira, Mariana Teodoro [UNESP]; Abe, Augusto Shinya [UNESP]; Rantin, Francisco Tadeu; Florindo, Luiz Henrique [UNESP] (Wiley, 2016)
The metabolic increment that occurs after feeding demands cardiovascular adjustments to be maintained, as increased heart rate (fH) and cardiac output. In mammals, postprandial tachycardia seems to be triggered by an increase in adrenergic activity and by nonadrenergic noncholinergic (NANC) factors, while in ectothermic vertebrates, this adjustment seems to be linked to a withdrawal of vagal drive as well as to NANC factors. Because the factors behind postprandial tachycardia have not yet been investigated in crocodilians, the present study sought to evaluate the postprandial tachycardia mediators in the broad-nosed caiman. To this end, fasting and digesting animals were instrumented with intraperitoneal cannula and subcutaneous electrocardiogram electrodes (for the measurement of fH, cardiac autonomic tones, and total fH variability, as well as for a power spectral analysis of fH). Data were then collected with the animals in an untreated state, as well as after muscarinic cholinergic blockade with atropine (2.5 mg kg–1) and after double autonomic blockade with atropine and propranolol (5.0 mg kg−1). Fasting animals’ fH was ∼18 bpm, a value which increased to ∼30 bpm during digestion. After the double autonomic blockade, fasting animals exhibited an fH of ∼15 bpm, while digesting animals’ fH was ∼23 bpm. This result is evidence of the presence of NANC factors with positive chronotropic effects acting during digestion. The calculated autonomic tones showed that, after feeding, the adrenergic tone increased while the cholinergic tone remained unchanged. Finally, fH variability analyses revealed that this adrenergic increase is primarily derived from circulating catecholamines.